IMPACT OF FUEL SUBSIDY REMOVAL ON NIGERIANS’ LIVING STANDARDS: A TWITTER-BASED ANALYSIS - Ifeduba, Emmanuel; Ebenezer Odion, Victor; Shakirat Ifedolapo, Adebisi (African Journal of Social and Behavioural Sciences, 2024)
This study examines the impact of fuel subsidy removal on the living standards of Nigerians, with a particular focus on conversations on Twitter (now X). Following the government’s decision to eliminate oil subsidies, there are growing concerns about rising fuel prices and their effects on daily life. This research employs contents analysis of tweets related to this policy shift, spanning from the Goodluck Jonathan administration to the present. The objectives are threefold: to evaluate how subsidy removal has influenced the cost of living, to identify prevalent public concerns and sentiments, and to explore coping mechanisms discussed online. The findings indicate a significant rise in living costs, with users expressing frustration, anger, and despair regarding inflation and decreased purchasing power. Many lower-income individuals feel disproportionately affected, highlighting the policy’s broader socioeconomic implications. Coping strategies shared among users reveal a resilient yet strained population adapting to new economic realities. This analysis underscores the importance of considering public sentiment in policymaking and suggests the need for targeted interventions to support vulnerable groups amid ongoing economic challenges.